Determinantes dos homicídios no Brasil - Frota, Marcos Tadeu Ellery (2014)
The violence is characterized as a serious social problem. In this contex the increase of deaths by homicide expresses the increase in violence and as a result puts the need to understand why this increase occurs. Homicides can be caused by several factors present in different instances and involve socioeconomic, demographic, cultural and political issues. This study aimed to analyze the determinants of the homicide rate in Brazil, contributing to a better understanding of the factors associated with these, in order to provide managers of public health and security information and knowledge about this phenomenon and enable the planning of control strategies and reducing the impact of the murders. Study of quantitative approach, analytical cross-sectional ecological type, considering the units of analysis states and the Federal District of Brazil. Homicide rates were calculated using the number of homicides for the period of 2002-2012.Historical series of homicide rates in Brazil were built. Association rate of homicides with explanatory variables in the bivariate analysis isolated by simple line regression was estimated. The independent variables were divided in to three groups: Socioeconomic indicators, criminal factors and public safety system. Statistically significant correlation variables proportion of households with income below the poverty line and extreme poverty, percentage of poor enrollment rate in secondary level education, income HDI, education HDI, criminality rate and percentage of expenditure on security public. Showed no statistically significant correlation: the Gini Coefficient, fertility rate, percentage of population with piped water rate, educational level, rate of effective military police and civilian police per capita, spending on Public Safety event, rate for possession narcotics, rate of occurrence of drug traffic in gang rate of occurrence for illegal possession of weapons. The variable that had the highest coefficient of determination was the punishment rate (R ² =0.57). The improvement of socioeconomic factors was of great social gain, but showed up as a central factor in reducing homicides. Large investments in effective law enforcement without improving investigation and prosecution of the perpetrators are not justified. The central issue is impunity.